Analysis of the Implementation of Zakat as a Fiscal Instrument in Supporting Islamic Economic Development in Indonesia - Delia Desvianti; Mercy Gusriyani; Suci Hijriyati; Zulfikar Hasan (al-Afkar, Journal For Islamic Studies, 2025)
This study analyzes the implementation of zakat as a fiscal instrument in supporting Islamic economic development in Indonesia. Zakat, as one of the pillars of Islam, has great potential to contribute to economic development and social welfare. In the context of Indonesia, which has the largest Muslim population in the world, effective implementation of zakat can have a significant impact. This study uses a qualitative method with literature study, reviewing various sources including journals, books, research reports, and other relevant literature. The analysis was conducted using an interactive approach to understand the concept of zakat, its potential application as a fiscal instrument, as well as the challenges and opportunities faced. The results of the study indicate that zakat has an important role as a fiscal instrument that can support Islamic economic development in Indonesia. Zakat can function as a source of additional income for the state, help reduce economic and social disparities, and encourage community economic empowerment. However, there are challenges related to regulations, institutions, and lack of public awareness that need to be addressed. Nevertheless, this study identifies great opportunities in the implementation of zakat as a fiscal instrument, along with the enormous potential of zakat in Indonesia and increasing public awareness. By making efforts to overcome existing challenges, zakat can be optimized as an effective fiscal instrument in supporting inclusive and sustainable Islamic economic development in Indonesia.